Efektivitas Sistem Pengendalian Internal dalam Pendeteksian dan Pencegahan Fraud di Lingkungan Perguruan Tinggi - Satria Negara, Hari Kusuma (Jurnal Solusi, 2019)
The purpose of this study is to reveal potential fraud symptoms occurred in the university environment and the role of internal auditors in detecting and preventing fraud. This research was conducted with a qualitative approach. Source data used are primary data. Determination the source of the data in a qualitative study using purposive sampling. Respondents in this study consisted of a team of Quality Assurance Agency and a Lecturer who once served as an internal auditor in the Quality Assurance Agency. The results showed at University many internal auditor conduct examine final report. Regulation of Minister Research, Technology and Universtiy Indonesia and the other regulation expected every University able to detect and reduce and prevent fraud. develop an effective internal Control System so as to prevent fraud. Prevention will be effective if the Rectoras the leader of University have Operational Prosedur Standar is done carefully.